Increased FGF-19 levels following explantation in women with breast implant illness - S. Azahaf; K. A. Spit; C. J. M. de Blok; P. W. B. Nanayakkara (Scientific Reports)
Abstract Breast Implant Illness (BII) is characterized by a cluster of systemic and local symptoms affecting a subset of women with silicone breast implants. While symptom improvement is frequently observed following implant removal, the underlying mechanisms remain poorly understood, and the absence of reliable biomarkers complicates clinical decision-making. Here, we investigate inflammatory protein profiles in 43 women with BII, comparing pre- and post-explantation levels using the Olink Target 96 Inflammation panel and Meso Scale Discovery technology for absolute quantification. Sixteen inflammatory proteins, including MCP-1, CD8A, and CCL11, were elevated post-explantation, with FGF-19 showing the most pronounced increase (64%). FGF-19 levels increased from a median of 136 pg/mL to 195 pg/mL (p = 0.001), comparable to levels in women with silicone breast implants but no BII. We propose that explantation may alleviate FGF-19 signaling disruption, restoring its metabolic benefits. These findings suggest FGF-19 as a potential diagnostic and therapeutic marker for BII, warranting further investigation.